Acute appendicitis - One of the causes of peritonitis in newborn - A case report with literature review - Olszanicka, Anna; Kołodziejczyk, Kacper; Branewska, Justyna; Ostrowska, Barbara; Matysek, Mikołaj; Imioło, Jan; Maciąg, Anna; Niemiec, Rafał; Hop, Izabela; Galas, Adam (Journal of Education, Health and Sport, 2023)
INTRODUCTION. Acute appendicitis is the most common reason for abdominal surgery in children however in newborn and infants it’s casuistics. It is also the most common surgical emergency in pregnancy. Right lower abdominal pain, abdominal stiffness, and periabdominal pain radiating to the right lower abdomen are the best signs to diagnose acute appendicitis in adults. Absence Or attenuation of intestinal murmurs, positive sternal muscle signs, positive blunt signs, and positive Rovsing’s Sign are the most reliable signs for the diagnosis of acute appendicitis in children. PURPOSE. The aim of the study is to show diagnostic difficulties of acute appendicitis in newborns and infants. It is one of the main differential diagnoses of unclear abdominal conditions. The smaller the child, the less characteristic the symptoms. A CASE REPORT. The study analyzes a male newborn born in the 37th week of pregnancy by caesarean section. Prenatal and family history of siblings’ illnesses. In whom, on the 11th day of life, symptoms of food intolerance were found, green deposits were noticed in the stomach probe, and the presence of blood in the stool. Intraoperatively, gangrenous perforated appendix with diffuse peritonitis was found. Acute appendicitis is rarely considered in newborns and infants as the etiological factor of acute peritonitis. However, the presented patient with a genetic defect. CONCLUSION. Acute appendicitis is a common phenomenon in childhood, but this diagnosis is rarely considered in the differential diagnosis of acute abdomen in the neonatal period, is more common in premature babies. The clinical picture of neonatal acute appendicitis is unspecific and may lead to delayed diagnosis and misdiagnosis of necrotizing enterocolitis, which is a much more common condition in the neonatal period. We would like to present the diagnostic difficulties, course of treatment, and complications associated with neonatal appendicitis.